2015
DOI: 10.1111/idh.12172
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer screening: knowledge is not enough

Abstract: Early detection of oral cancer reduces mortality rates so there is a professional responsibility to ensure that comprehensive oral cancer screenings are being performed on patients. Dental hygienists may not have the authority in a dental practice to overcome all of the barriers that are preventing them from performing these screenings. Public awareness about oral cancer screenings could increase the demand for screenings and thereby play a role in changing practice norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 13 publications
(36 reference statements)
2
34
1
1
Order By: Relevance
“…Consequently, there may be situations where GP nurses recognize the need for opportunistic screening but lack the volitional control to do. These findings are consistent with other specialty areas including cervical cancer screening, oral cancer screening and nutritional screening, where discord between organizational cultures preclude HCP from implementing evidence‐based screening practices and create a dissonance between personal beliefs and practice behaviours.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, there may be situations where GP nurses recognize the need for opportunistic screening but lack the volitional control to do. These findings are consistent with other specialty areas including cervical cancer screening, oral cancer screening and nutritional screening, where discord between organizational cultures preclude HCP from implementing evidence‐based screening practices and create a dissonance between personal beliefs and practice behaviours.…”
Section: Discussionsupporting
confidence: 86%
“…Many risk factors for OC have been described, but smokeless and smoking tobacco, alcohol, and viral infection especially human papillomavirus (HPV) are among the fundamental factors for disease occurrence (Johnson et al, ; Somatunga et al, ). The diagnosis of OC in the early stage and subsequently early intervention with the required therapy have a positive impact on increasing the rate of survival up to 5 years (Lopez‐Jornet et al, ; Seoane et al, ; Tax et al, ). Fortunately, OC is one of the disease that can be discovered in the early stage through routine visual and tactile inspection of oral mucosa (Colella, Gaeta, Moscariello, & Angelillo, ).…”
Section: Introductionmentioning
confidence: 99%
“…An OCS can be performed at every dental hygiene visit, yet this process may not always be undertaken. A survey conducted in Nova Scotia expressed concern that OCS knowledge and beliefs do not always translate into comprehensive screenings . Several factors which may impede provision or quality of screenings have been identified, including lack of time, confidence, training and financial incentive .…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted in Nova Scotia expressed concern that OCS knowledge and beliefs do not always translate into comprehensive screenings . Several factors which may impede provision or quality of screenings have been identified, including lack of time, confidence, training and financial incentive . It has also been suggested that dental hygienists are discouraged from completing these screenings, as it is primarily the responsibility of the dentist .…”
Section: Introductionmentioning
confidence: 99%